2021
DOI: 10.1016/j.japh.2020.08.027
|View full text |Cite
|
Sign up to set email alerts
|

The role of outsourcing facilities in overcoming drug shortages

Abstract: Background: The Drug Quality and Security Act passed in 2013 created a new voluntary category of compounders, referred to as outsourcing facilities. The regulatory landscape allows these facilities to compound on a larger scale in comparison with the typical compounding pharmacies, which positions them to potentially serve a role in overcoming drug shortages. Objective: The purpose of this article is to identify the number of drug products on shortage as reported by the Food and Drug Administration (FDA) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Regardless of the method selected to overcome the current limited access to GLP-1 receptor agonists, educating patients and setting expectations during the transitional period is time well spent. Caution patients to consider the credibility and reliability of online sources and explain the concerns related to compounded products ( 4 , 5 ).…”
Section: Patient Education Through the Glp-1 Receptor Agonist Shortagementioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the method selected to overcome the current limited access to GLP-1 receptor agonists, educating patients and setting expectations during the transitional period is time well spent. Caution patients to consider the credibility and reliability of online sources and explain the concerns related to compounded products ( 4 , 5 ).…”
Section: Patient Education Through the Glp-1 Receptor Agonist Shortagementioning
confidence: 99%
“…Many social media sites and online clinics claim to offer commercially available GLP-1 receptor agonist medications or even compounded versions at a discounted price. Although compounded medications are regulated and generally considered safe ( 4 ), compounded GLP-1 receptor agonists are unique. Each GLP-1 receptor agonist is only available as a branded medication manufactured by a single company.…”
mentioning
confidence: 99%
“…This theme issue also contains 2 articles on 1 potential solution to the drug shortage problem, the use of outsourcing facilities. Mattingly 14 performed an investigation to determine the extent to which 503B outsourcing facilities were able to compound products for those reported as shortages by FDA. Data from July 2018 through December 2019 listed 64 outsourcing facilities, which compounded products matched only 27% of the API on the shortage list.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…For example, Hu verified the effectiveness of option contracts in the supply chain coordination process under demand uncertainty [ 37 ]; Aghajani et al used option contracts to derive the optimal production and purchasing quantities for supply chain decision makers under output and demand uncertainty [ 38 ]; Liu et al suggested that option contracts can increase the level of joint government-enterprise physical and production capacity stockpiles of emergency supplies and improve the response level of disaster relief [ 39 ]. However, while existing research confirms that option pacts can coordinate government-enterprise cooperation to carry out physical and production capacity stockpiling of emergency supplies, drugs in shortage belong to special emergency supplies, and the primary prerequisite for promoting the security of supply of medicines through enterprise production capacity stockpiling is an adequate stockpile of APIs [ 40 , 41 ]. The current shortage of APIs has become one of the main reasons for drug shortages in China, which is contrary to the reality of China as the world’s second-largest producer of APIs and the first-largest exporter of APIs [ 4 , 5 , 42 ].Various realities suggest that strengthening the API stockpile is the best way to realize the physical and production capacity of pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%